A Comparison Of Overburden Response Due To Longwall Mining - David K. Ingram (International Conference on Ground Control in Mining, 1994)
The objective of this U.S. Bureau of Mines (USBM) investigation was to characterize overburden response due to longwall mining. Subsurface strata and surface deformations were monitored at two sites in southeastern Ohio. Site A included two adjacent longwall panels. Site B consisted of one longwall panel. Both sites had similar mine geometries and overburden thicknesses. The major difference between the two sites was the rock strata within the overburden. Multipoint borehole extensometers (MPBX) were employed to measure subsurface displacements. Survey monuments were installed above the centerline and profile of each panel to measure surface deformations. Subsidence of the surface was observed before and after movement was detected in the MPBX units. Initial and final displacement of the MPBX units occurred at the same time at both sites. No deformation was detected outside the panel area. The development of overburden deformation was different over each panel. The final subsurface failure characteristics also varied between panels.